Diagnostic Approach and Treatment of Choledocholithiasis - Indah Gianawati; Ali Sulaiman; L A Lesmana; Toar JM Lalisang; Arman A Abdullah (The Indonesian Society for Digestive Endoscopy, 2004)
Choledocolithiasis may cause acute cholangitis which is life-threatening condition. It has non specific clinical signs from mild to severe condition such as septicemia. Diagnostic and treatment modalities had developed a great deal recently. Therapeutic options include endoscopic retrograde cholangio pancreatography (ERCP),common bile duct exploration (CBDE), laparoscopic CBDE and stone retrieval. The important thing is to choose the appropriate method for each patient. We reported a case of choledocolithiasis in 40 years old, male patients who was clinically diagnosed as acute cholangitis. Diagnostic approach to find the etiology was done. Abdominal USG and CT were performed and showed multiple stones in gallbladder and intrahepatic biliary duct, suspected mass at caput of the pancreas and hepatomegaly. The ERCP showed dilatation of intra and extra hepatic biliary ducts with multiple stone in common bile duct (CBD), hepatic duct and gallbladder. The stent was placed for biliary drainage. The patient underwent cholecystectomy per laparoscopy, but further evaluation of the cholangiography still showed the presence of stones in intrahepatic biliary duct. Laparotomy exploration of CBD was done and it revealed multiple stones and dilatation of distal CBD. Surgical treatment selected for this case was choledocojejunostomy. Keywords: Choledocolithiasis, CBD, diagnostic approach